Wakaf Produktif dan Sustainability: Membangun Bisnis yang Berkelanjutan - Jarwadi, Arinal_Haq (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2025)
This article discusses the relationship between productive waqf to build a sustainable waqf business product. Through a literature study to find out how the management process in previous research is able to make waqf productive so that business sustainability is created. The results of several productive waqf models are able to implement sustainable businesses with capital obtained from productive waqf funds even though there are obstacles and challenges that arise, but when viewed from the perspective of opportunity, it is very large because the business model can be anything such as agriculture, UMKM funding, blockchain waqf, stock waqf and so on.